Дослідження методів збирання вимог в IT-проєктах - Степченко, А. О. (ХНУРЕ, 2024)
This work is devoted to the study of current problems at the requirements elicitation stage, the reasons for their occurrence and the development of recommendations for their prevention. Clearly defined requirements enable effective project planning and control, reducing the risk of failure. However, gathering requirements often faces delays due to changing technological environments and stakeholder interactions, necessitating a tailored approach. It is proposed to create universal ensembles of methods for requirements elicitation depending on the classification of the project, which will help optimize the use of resources and ensure successful project results, increasing competitiveness in the IT industry.
Keywords: IT-проєкт; збирання вимог в іт-проєктах